China’s ratification of the agreement on port state measures to prevent, deter and eliminate illegal, unreported and unregulated fishing: driving factors, challenges and possible pathways - Chen, Xidi; Wang, Lei (Frontiers in Marine Science, 2025)
Following years of preparatory efforts and evaluation, China formally acceded to the Agreement on Port State Measures to Prevent, Deter and Eliminate Illegal, Unreported and Unregulated Fishing (PSMA) on April 16, 2025, marking a new advancement in its ongoing campaign against IUU fishing and the conservation of marine fisheries. This study examines China’s potential contents for joining the PSMA, identifies implementation challenges, and proposes actionable solutions to amplify its role as a responsible fisheries nation within the PSMA framework. Findings indicate that China’s accession aligns with its national agenda to modernize distant-water fisheries under the “ecological civilization” paradigm, aiming to bolster its influence in global fisheries governance, strengthen multilateral cooperation, and advance contributions to sustainable use of fishery resources. The analysis reveals persistent challenges in four domains: (1) incomplete domestic legal frameworks to meet PSMA obligations; (2) insufficient port-state management systems and enforcement capacities; (3) fragmented international coordination mechanisms; and (4) structural gaps between industrial expansion and sustainability goals. To address these, the study advocates a dual-track strategy. Domestically, priorities include legal and institutional reforms to harmonize with PSMA requirements, enhanced capacity building, and industry modernization. Internationally, China should lead in establishing regional port-state coordination platforms, institutionalize data-sharing partnerships, and promote equitable rulemaking within PSMA. These measures would enhance compliance while advancing China’s dual objectives of fostering sustainable fisheries and solidifying its role as a responsible global fishing contributor.